Implementation of Security and Monitoring System on Prototype Car based on Internet of Things (IoT) - Anggielita, Renata; Salamah, Irma; Suroso, Suroso (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
This Internet of Things (IoT)-based car security and monitoring system is implemented on a prototype car with a security system in the form of face identification, Global Positioning System (GPS), and Gas Sensor. The purpose of this research is to improve the security and safety of motorized vehicles, especially cars. This IoT-based car security system uses the prototype method, which is a system development technique that uses a prototype to describe the system so that users have a clear picture of the system to be built. From the results of testing face identification, gas sensors, and GPS show that the system can work according to the expected design. Based on the overall test results this system works quite well to improve vehicle security. therefore, this car security and monitoring system has a positive effect on making vehicle owners feel safe.